Upaya Meti (The Japanese Ministry Of Economy, Trade And Industry) dalam Mempertahankan Dominasi Perusahaan Otomotif Jepang di Indonesia - Achyar Arief Firdaus; Harza, Zulkifli (Palito, 2023)
The development of the world political economy cannot be separated from the role of the industrial sectors. Japan is ones countries that the relies on the industrak sectors to support the national economy is namely the automotive industry. Indonesian has been a market for the Japan automotive industyry since the 1960 decade and the situation continued unitil the decade 2000 years. On 2015-2020 years period is representation of development of the Indonesian automotive market is was mor complex when competitor appeared from China dan South Korean which caused concern from Japan because it could reduces that had been foprmed to so far. In Dealing with attack by automotive industry South Korean and China on Indonesian on national market, the Japanese Government, throught METI (The Japanese Monistry of Economy and Trade and Industry) then the provided mediation and the un-financial support to deal with competition in he automotive industry market with impresife strategy of automotive industry from China dan South Korean.